2010
DOI: 10.1152/ajpregu.00836.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of VEGF- and NO-dependent angiogenesis does not impair liver regeneration

Abstract: Angiogenesis occurs through a convergence of diverse signaling mechanisms with prominent pathways that include autocrine effects of endothelial nitric oxide (NO) synthase (eNOS)-derived NO and vascular endothelial growth factor (VEGF). However, the redundant and distinct roles of NO and VEGF in angiogenesis remain incompletely defined. Here, we use the partial hepatectomy model in mice genetically deficient in eNOS to ascertain the influence of eNOS-derived NO on the angiogenesis that accompanies liver regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…We did not observe any compensatory increase in iNOS protein or mRNA expression in eNOS −/− livers subjected to PH. Our studies confirm previous observations that the iNOS isoform does not compensate for eNOS deficiency in regenerating livers 25. Despite distinct impairments in hepatocyte proliferation, liver growth at 8 days post‐PH was comparable between WT and eNOS −/− livers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We did not observe any compensatory increase in iNOS protein or mRNA expression in eNOS −/− livers subjected to PH. Our studies confirm previous observations that the iNOS isoform does not compensate for eNOS deficiency in regenerating livers 25. Despite distinct impairments in hepatocyte proliferation, liver growth at 8 days post‐PH was comparable between WT and eNOS −/− livers.…”
Section: Discussionsupporting
confidence: 90%
“…Several recent studies suggest that eNOS is expressed in hepatocytes, in addition to endothelial cells, in the liver 6‐10. However, previous studies with eNOS −/− mice have led to conflicting findings on its potential roles in hepatocyte proliferation in response to PH 10, 25. Recently, Vasquez‐Chantada et al described a role for LKB1‐AMPK in HGF‐induced eNOS phosphorylation in hepatocytes and impaired BrdU incorporation in response to PH in eNOS −/− , as compared to WT 10.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, AR have attracted attention for their contribution to angiogenesis. However, the underlying mechanism regarding the modulation of AR on the secretion of VEGF and NO remain unrevealed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other factors that could play a role in organizing the microarchitecture of the liver. These include among others, the induction of endothelial cell proliferation by VEGF or NO [6,7], the production of Wingless (Wnt) and hedgehog (Hh) ligands by hepatocytes and liver sinusoidal cells [8], and the secretion of TGF-b, a negative regulator of hepatocyte proliferation [1]. In addition, EM produced could play a key role in harboring growth factors (i.e.…”
mentioning
confidence: 99%
“…What is the role of VEGF in sustaining sinusoidal endothelial cells? Shergill et al [6] showed that in a mouse model of liver regeneration post-hepatectomy, inhibition of VEGF and NOdependent angiogenesis did not impair liver regeneration. However, in a model of regeneration post-acetaminophen toxicity, Donahower et al [7] showed that the administration of recombinant VEGF reduced necrosis and enhanced hepatocyte regeneration.…”
mentioning
confidence: 99%